Construction and validation of a bone marrow tissue microarray. Issue 1 (12th May 2006) - Zimpfer, Annette; Schönberg, Sharon; Lugli, Alessandro; Agostinelli, Claudio; Pileri, Stefano A; Went, Philip; Dirnhofer, Stephan
Abstract : Background: The use of tissue microarrays (TMAs) is now a generally accepted method for the investigation of solid tumours. However, little is known about the applicability of the TMA technique for analysis of patients with acute leukaemia. A bone marrow (BM)-TMA analysis with 15 different immunohistochemical markers was performed. The TMA was validated by comparison with the corresponding full tissue sections. Materials and methods: A BM-TMA comprising 148 cases of acute leukaemia, including 115 acute myeloid leukaemia (AML) and 33 acute lymphoblastic leukaemia (ALL) cases, was constructed. Expression of CD3, CD10, CD15, CD20, CD34, CD61, CD68, CD79a, CD99, CD117, CD138, myeloperoxidase, haemoglobin A1, glycophorin and terminal deoxynucleotidyl transferase was immunohistochemically analysed. 50 cases of the TMA were directly compared with the corresponding full tissue section to validate the results. Results: Morphologically and immunohistochemically, 6 (4%) of 148 cases and 765 (11%) cores of 6912 individual analyses were not evaluable. A direct comparison of TMA cases with conventional full sections showed a concordance of the results of 100%. Conclusions: The small size of bone-marrow biopsies and the presence of bony trabeculae do not preclude construction and analysis of acute leukaemia TMAs. Acute leukaemia cases on TMA displayed the characteristic phenotypic profiles expected in different AML and ALL subtypes. Therefore, the TMA technique is also a promising method for high-throughput analysis of combined marker expression and clinicopathological correlations in patients with leukaemia.